Mitigasi Fraud pada Lembaga Pendidikan Berbasis Islam (Studi Kasus Sekolah-sekolah di Kabupaten Klaten) - Puspa Sari, Kiki; Kuntaryanto, Oki; Susyanti, Susyanti (Widya Dharma Journal of Business - WIJoB, 2025)
This study aims to determine whether ethical leadership (X1), the whistleblowing system (X2), internal control (X3), ethical values (X4), and religiosity (X5) influence fraud mitigation (Y). Data collection was conducted by distributing questionnaires to 160 respondents, with 120 completed questionnaires returned. The analysis methods used in this study include descriptive analysis, instrument testing (validity and reliability tests), classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test), and statistical tests (t-test, F-test, and coefficient of determination test). The findings of this study indicate that ethical leadership has a positive effect on fraud mitigation, the whistleblowing system has no effect on fraud mitigation, internal control has a positive effect on fraud mitigation, ethical values have a positive effect on fraud mitigation, and religiosity has a positive effect on fraud mitigation.